A ANALISIS KOMPETENSI NAVIGASI TARUNA POLIMARIM MELALUI PEMBELAJARAN BERBASIS BRIDGE SIMULATOR: Indonesia - Asce Patongloan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the improvement of navigation competence of cadets at Politeknik Maritim AMI Makassar (Polimarim AMI) through Bridge Simulator-based learning. Navigation competence is a fundamental skill that maritime cadets must master to meet the Standards of Training, Certification and Watchkeeping for Seafarers (STCW), 2010 Manila Amendments. This research used a quantitative approach with a quasi-experimental one-group pretest-posttest design, involving 30 Nautika Study Program cadets selected through purposive sampling. Navigation competence was measured with a performance-based assessment rubric covering collision avoidance, chart-work and position fixing, radar and ARPA operation, and bridge resource management, administered before and after a structured Bridge Simulator training program. Data were analyzed using a paired-sample t-test and the normalized gain (N-Gain) score. The results indicate a statistically significant increase in navigation competence scores after the Bridge Simulator-based learning intervention, with an average N-Gain score in the moderate-to-high category, the largest gain occurring in the chart-work and position fixing indicator. These findings suggest that Bridge Simulator-based learning is effective for strengthening cadets' practical navigation skills prior to sea practice (Praktek Laut), and it is recommended that maritime education institutions integrate structured, progressively challenging simulator scenarios more intensively into their nautical curricula.